The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1088/1742-6596/1916/1/012003
|View full text |Cite|
|
Sign up to set email alerts
|

Power Generation Using Sound by Piezo Electric Material

Abstract: Pollution is a major problem all over the world. According to the energy conservation statement law states that energy cannot be created or destroyed but can be converted from one form to another. As it relates to nature, the sudden increase in urban and industrial growth has been completed with potentially hazardous waste. Sound is the electrical energy of the machine and can be converted into electrical energy through many provocative methods including heating using piezoelectric material and diaphragm. Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The "A" level microphone is used as a basic sound measuring instrument as shown in figure 2' around the vehicle cluster where the Motor is placed. The fast Fourier frequency spectrum is typically employed for the analysis of noise wavelengths in BLDC motors [21]. Noise signature analysis precisely identifies the sources of noise, including airflow, the motor itself, and the surrounding environment.…”
Section: Sound Fields In Vehicle Environmentmentioning
confidence: 99%
“…The "A" level microphone is used as a basic sound measuring instrument as shown in figure 2' around the vehicle cluster where the Motor is placed. The fast Fourier frequency spectrum is typically employed for the analysis of noise wavelengths in BLDC motors [21]. Noise signature analysis precisely identifies the sources of noise, including airflow, the motor itself, and the surrounding environment.…”
Section: Sound Fields In Vehicle Environmentmentioning
confidence: 99%
“…SWIPT has the potential to revolutionize various fields, such as WSNs, Internet of Things (IoT) devices, and even mobile communications 15 . The ability to convert ambient sound energy into usable electrical power has opened innovative avenues for sustainable energy harvesting 16 . The basic principle of acoustic energy harvesting involves using transducers or devices that can convert mechanical vibrations induced by sound waves into electrical energy 17 .…”
Section: Introductionmentioning
confidence: 99%
“…15 The ability to convert ambient sound energy into usable electrical power has opened innovative avenues for sustainable energy harvesting. 16 The basic principle of acoustic energy harvesting involves using transducers or devices that can convert mechanical vibrations induced by sound waves into electrical energy. 17 These transducers often use piezoelectric materials, which generate electric voltage when subjected to mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…All of the following parameters: current frequency (Hz), RMS current (A), and threshold (%) are compared on the MATLAB/Simulink platform for signal analysis [23]. MATLAB/Simulink is employed to simulate and evaluate the overall energy contribution of noise in energy dissipation in BLDC motors marked as okay [24][25][26]. Readings are typically collected at the stable speed state of the BLDC motor, where the noise-embedded frequency is higher [27].…”
Section: Introductionmentioning
confidence: 99%
“…Virlan Bogdan et al, (2021) developed special software for increasing motor speed at low resistance torque, employing 24 stator slots and 22 rotor permanent magnets [25]. Zhaoyang Fu et al, (2021) investigated fault signal diagnosis methods for dual redundancy BLDCM winding fault analysis [26]. Chaithanya D et al, (2021) demonstrated the conversion of sound, a non-continuous form of energy, into electrical energy using piezoelectric material [26].…”
Section: Introductionmentioning
confidence: 99%